Molecular Semiconductors for Logic Operations: Dead‐End or Bright Future?. Issue 10 (22nd January 2020) - Schweicher, Guillaume; Garbay, Guillaume; Jouclas, Rémy; Vibert, François; Devaux, Félix; Geerts, Yves H.
Abstract: The field of organic electronics has been prolific in the last couple of years, leading to the design and synthesis of several molecular semiconductors presenting a mobility in excess of 10 cm 2 V −1 s −1 . However, it is also started to recently falter, as a result of doubtful mobility extractions and reduced industrial interest. This critical review addresses the community of chemists and materials scientists to share with it a critical analysis of the best performing molecular semiconductors and of the inherent charge transport physics that takes place in them. The goal is to inspire chemists and materials scientists and to give them hope that the field of molecular semiconductors for logic operations is not engaged into a dead end. To the contrary, it offers plenty of research opportunities in materials chemistry. Abstract : Organic semiconductors for logic operation are currently facing a crisis because charge carrier mobility tends to level off, the industrial interest is fading away, and more than half of transport measurements in transistors are stained by errors. However, the field remains particularly rich in opportunities for new academic and even industrial developments if fundamental issues are addressed.